Molecular biology of canine parainfluenza virus V protein and its potential applications in tumor immunotherapy - Cheng, Huai; Zhang, Hewei; Cai, Huanchang; Liu, Min; Wen, Shubo; Ren, Jingqiang (Frontiers in Microbiology, 2023)
Canine parainfluenza virus (CPIV) is a zoonotic virus that is widely distributed and is the main pathogen causing canine infectious respiratory disease (CIRD), also known as “kennel cough,” in dogs. The CPIV-V protein is the only nonstructural protein of the virus and plays an important role in multiple stages of the virus life cycle by inhibiting apoptosis, altering the host cell cycle and interfering with the interferon response. In addition, studies have shown that the V protein has potential applications in the field of immunotherapy in oncolytic virus therapy or self-amplifying RNA vaccines. In this review, the biosynthesis, structural characteristics and functions of the CPIV-V protein are reviewed with an emphasis on how it facilitates viral immune escape and its potential applications in the field of immunotherapy. Therefore, this review provides a scientific basis for research into the CPIV-V protein and its potential applications.